1993
DOI: 10.1037/0882-7974.8.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about strategies during, before, and after making a decision.

Abstract: Two studies examined the impact of think-aloud and self-report instructions on the decision-making performance of young and older adults. Findings from Study 1 indicated that think-aloud instructions increased total time to decision for young and older adults but did not otherwise affect decision-making processes. Counter to predictions, the only significant interaction effect indicated that young adults in the think-aloud condition more frequently rechecked information than older adults. Findings from Study 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
73
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 23 publications
14
73
0
3
Order By: Relevance
“…However, giving verbal reasons in practice significantly reduced mistakes. Similar results were found by Berardi-Coletta (1990;Berardi-Colletta et aI., 1995), Allwood (1990), andJohnson (1993). These findings lend support to the idea that the verbal component of verbal reason giving is not the critical component affecting performance.…”
Section: Issues Surrounding Computer Usesupporting
confidence: 80%
“…However, giving verbal reasons in practice significantly reduced mistakes. Similar results were found by Berardi-Coletta (1990;Berardi-Colletta et aI., 1995), Allwood (1990), andJohnson (1993). These findings lend support to the idea that the verbal component of verbal reason giving is not the critical component affecting performance.…”
Section: Issues Surrounding Computer Usesupporting
confidence: 80%
“…(Streufert et alii, 1990). Plusieurs études empiriques ont validé cette hypothèse dans les domaines de l'achat automobile et de la location d'appartements (Johnson, 1990(Johnson, , 1993. En parallèle, ces recherches soulignent la Certains auteurs ont proposé une autre hypothèse : l'aversion au risque augmenterait avec l'âge.…”
Section: L'effet Additif Des Manifestations Objectives Et Subjectivesunclassified
“…In another line of studies, Johnson [1993] showed that older (vs. younger) adults examined less information prior to selecting an apartment for rent, and she demonstrated that older (vs. younger) adults spent more time reviewing information, used less information, and re-evaluated information more frequently when making a simulated car-purchasing decision [Johnson, 1990]. In a related study, Chen and Sun [2003] compared older and younger adults on a yard sale task, designed to simulate the dowry problem.…”
Section: Bounded Rationality Cognition and Older Adults' Decision Mmentioning
confidence: 99%